BA.plot: An R function for Bland-Altman analysis - Kalesh M. Karun; Amitha Puranik (Elsevier, 2021)
Bland-Altman analysis is a very commonly used method in the biomedical research. This method is used to study the agreement between two measurements that are in continuous scale. Although this method is commonly used in medical research, the statistical software packages do not have the menu-driven operation for the Bland-Altman analysis. Hence this paper intends to provide an R function (BA.plot) for Bland-Altman analysis.